Onderwy svoorsiening in die Repu- bliek van Suid-A frika vir die komende dekades opgron d van die Raad vir Geesteswetenskaplike Navorsingse konsep onderwysbeginsels - Barnard, S. S. (Koers, 1981)
In June 1980 the Cabinet requested the HSKC to initiate a penetrating study ofthe total educlional situation in (he RSA. The request was put that “guidelines o f principle" be recommended to serve as a basis for incipient decisionmaking as regards equal educationalfacilitiesfor all the inhabitants o f the country. The recommended principles are encompassed in paragraph 2.3 o f the “Report o f the Main Committee o f the HSRC investigation ofeducation” which was handed to the Minister o f National Education on 30 July 1981. The final revised eleven principles on which consensus was reached were preceded by 12 draft proposals (two o f which were incorporated so that in the final form there would be only evelen). In this article an attempt is made to evaluate the original twelve principles on the basis o f principle and educational value.